Nonlinear Strong Coupling by Second‐Harmonic Generation Enhancement in Plasmonic Nanopatch Antennas. Issue 16 (29th May 2022) - Krause, Bryson; Mishra, Dhananjay; Chen, Jiyang; Argyropoulos, Christos; Hoang, Thang
Abstract: Enhanced electromagnetic fields within plasmonic nanocavity mode volumes enable multiple significant effects that lead to applications in both the linear and nonlinear optical regimes. In this work, enhanced second‐harmonic generation (SHG) is demonstrated from individual plasmonic nanopatch antennas (NPAs) which are formed by separating silver nanocubes from a smooth gold film using a sub‐10 nm zinc oxide spacer layer. When the NPAs are excited at their fundamental plasmon frequency, a 10 4 ‐fold increase in the intensity of the SHG wave is observed. Moreover, by integrating quantum emitters that have an absorption energy at the fundamental frequency, a second‐order nonlinear exciton–polariton strong coupling response is observed with a Rabi splitting energy of 19 meV. The nonlinear frequency conversion using NPAs thus provides an excellent platform for nonlinear control of the light−matter interactions in both weak and strong coupling regimes which will have a great potential for applications in optical engineering and information processing. Abstract : This work demonstrates a 10 4 ‐fold enhancement of second‐harmonic generation from individual plasmonic nanopatch antennas (NPAs). By integrating quantum emitters that have an absorption energy at the fundamental frequency, a second‐order nonlinear exciton–polariton strong coupling response is demonstrated. Plasmonic NPAs provide an excellent platform for nonlinear control of the light−matter interactions and promise a wealth of potential for applications in optical engineering.